Fidelity of an Educational Intervention to Prevent Human Papillomavirus in Adolescents - Garcia-Inzunza, Jaime Adalberto (2025)
Introduction: Human papillomavirus (HPV) is one of the most prevalentsexually transmitted infections, with significant implications for publichealth. Adolescence is a key stage for implementing preventive educationalinterventions that promote responsible sexual behavior. Therefore, theobjective was to evaluate the fidelity of an educational intervention for theprevention of HPV in adolescents.Matherial and Methods: non-experimental, descriptive, cross-sectionalstudy was conducted with a convenience sample of 393 14-year-oldsecondary school students. The intervention consisted of participatoryeducational sessions focused on sexual and reproductive rights. Interventionfidelity was assessed by considering the retention rate, compliance rate,and the instructor and program quality evaluation scale. Participants wereevaluated using a Likert-type scale to measure acceptability and satisfaction,with one indicating low satisfaction and five indicating very satisfied.Results: suggest that the HPV prevention program was successfullyimplemented, showing an average session completion rate of 89.11%, anacceptability rate of 97.7%, and high participant satisfaction (M = 4.502,SD = 0.627). The content, activities, and facilitators were well received andadapted to their needs.Conclutions: The structure and design of the intervention program areeffective and feasible to evaluate whether the intervention is truly achievingits main objective.